Användning av dietfoder till hundar och katter på Smådjurskliniken vid SLU - Engström, Annica (SLU/Dept. of Animal Environment and Health (until 231231), 2006)
During one week (9-13 May, 2005) the use of veterinary diets for the hospitalised patients att the University clinic was registered. The animal owners were interviewed by telephone six months later about the feeding after coming home.